Evolving a Holistic Management Strategy for Forest Resources - Singh, Jarnail (Indian Forester, 1998)
The National Forest Policy 1988 envisages a holistic and professional strategy of forest management for achieving the objectives enunciated therein. The traditional forest management approach (Working Plan) provides silvicultural treatment on sustained yield basis which is far inadequate considering the present scenario of resource conditions and policy objectives. The proposed Strategy of Forest Management is based on holistic treatment of an ecosystem on Watershed pattern. it stresses integral and site-specific treatment offorest resources. The strategy incorporates overall planning for macro-unit the entire landscape of a District as well as site-specfic planning for micro unit. It provides modes to extend the forest cover to non-forest areas. It is an effort to provide natural management to the forest areas in their natural settings. Once the strategy assumes its natural form it will provide a lasting solution to the problem of management planning of forest resources for sustainable management.